Pengetahuan Remaja tentang Risiko Pernikahan Dini: Teenagers' Knowledge about the Risks of Early Marriage - Supriandi Supriandi; Gusvira Rosalina; Berthiana Berthiana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Teenagers are the generation who are hoped to succeed and make a positive contribution to the nation's development. Being a teenager starts from 10 to 19 years old. Early marriage is when one or both couples are still under 19. To determine teenagers' knowledge about early marriage's risks according to their age and education. A literature review was the method of this research. The findings through Google Scholar using Keywords by MeSH found 97 journals included in 3 journals. This research adopted a quantitative design and used a cross-sectional approach.